Measuring the effect of transaction costs for investment in irrigation pumps: Application of unobserved stochastic threshold model to the case of Nigeria - Takeshima, Hiroyuki; Adeoti, Adetola I.; Salau, Sheu (International Food Policy Research Institute, 2010)
Small-scale private irrigation schemes (SPRI) have been the driving force behind the expansion of irrigated areas in Nigeria, despite government efforts to promote large-scale public irrigation schemes. SPRI allows adjustment of irrigation schedules in accordance with observed crop needs. The irrigated area in Nigeria is, however, far below its potential and an increase in farmers' investment in irrigation is essential. While Nigerian farmers' low level of investment in irrigation may be partly due to low returns, it is also the result of high transaction costs associated specifically with making such an investment. Although reducing transaction costs is important because the reduction provides farmers with a more enabling environment, transaction costs are often unobservable and little is known about what factors contribute to them. This article empirically assesses the effect of unobserved transaction costs for Nigerian farmers' when investing in irrigation pumps, using the baseline survey data for the Second Fadama Development Program (Fadama II). The results indicate that the unobserved transaction costs are higher for female landless farmers, with higher dependency ratio and residing far from town. The results suggest that the unobserved transaction costs can be as important as the factors determining the profitability of irrigation pump, emphasizing the importance of reducing transaction costs in addition to improving the environment for higher return from irrigation investment.